IMPROVING COORDINATION SKILLS IN 10-11 YEAR OLD STUDENTS USING SIMULATION TECHNOLOGIES - Sablin A.B. ,; Ulyanova E.A. ,; Latak A.I. ,; Popova N.Y. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop coordination skills in primary school children using the imitation aid "coordination ladder". Methods and structure of the study. The pedagogical experiment involved 104 students, students in the 2nd grades of a comprehensive school, aged 10-11 years. The study was conducted during the school year, the children attended physical education lessons twice a week, the duration of the lessons was 40 minutes. Children from the control group (grades 2A and 2B) were engaged in physical education at school according to the standard school program for physical education. And children from the experimental group (grades 2B and 2G) during the physical education lesson additionally performed a set of physical exercises on the coordination ladder for 5-6 minutes. Results and conclusions. At the end of the study, the indicators in the "jumping in place" test in the control group improved from 14.3±1.9 to 15.6±2.0, the increase in indicators was 9.1% (p>0.05). This is due to the duration of the pedagogical experiment, the effectiveness of the standard program and a favorable period for the development of coordination abilities in primary school age. In the experimental group, the indicators of the ability to connect movements improved from 13.1±2.1 to 16.9±1.8, the increase in indicators was 29.2% (p<0.05). This proves the effectiveness of using the coordination ladder in the educational process of students aged 10-11 years. Thus, the effectiveness of using the coordination ladder in physical education lessons at school with children aged 10-11 years has been proven. A set of physical exercises on the coordination ladder is recommended for use in each physical education lesson at school as a supplement to the standard school program.